IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR KOTA MATARAM - I Wayan Getas; I Wayan Budiartha (Padma Sari: Jurnal Ilmu Pendidikan, 2026)
This study originates from the discourse in the field of education, particularly in curriculum development and elementary school learning. The Merdeka Curriculum has emerged as a new paradigm in Indonesian education, emphasizing flexibility, differentiation, and the strengthening of students’ character. One crucial issue examined in this research is how the implementation of the Merdeka Curriculum contributes to enhancing students’ learning independence, especially at the elementary level. The purpose of this article is to analyze the application of the Merdeka Curriculum in Mataram City and to assess the extent to which this curricular innovation fosters students’ autonomy in the learning process. The research employed a qualitative method with a case study approach in several elementary schools in Mataram. Data were collected through classroom observations, interviews with teachers and students, and documentation of lesson planning. The hypothesis proposed is that the implementation of the Merdeka Curriculum significantly influences the development of learning independence through project-based learning, differentiation, and providing opportunities for students to explore their interests. The findings reveal that students learning under the Merdeka Curriculum demonstrate increased initiative, decision-making skills, and self-reflection abilities. Teachers play a vital role as facilitators who guide without limiting students’ creativity. The contribution of this research lies in enriching the literature on the effectiveness of the Merdeka Curriculum while offering practical recommendations for educators and policymakers. These results highlight the importance of the Merdeka Curriculum as a relevant educational strategy to foster learning independence from an early stage, preparing future generations to be adaptive, critical, and competitive.